Receptores tensoriais com processamento distribuído para sistemas de comunicações cooperativos - Sousa, Igor Flávio Simões de (2014)
In this dissertation, we present a distributed data estimation and detection approach for the uplink of a network that uses CDMA at transmitters (users). The analyzed network can be represented by an undirected and connected graph, where the nodes use a distributed estimation algorithm based on consensus averaging to perform joint channel and symbol estimation using a receiver based on tensor signal processing. The centralized receiver, developed for a central base station, and the distributed receiver, developed for micro base stations, have their performances compared in a heterogeneous network. Then, two tensor-based receivers are proposed to be used in a relay-assisted network. In this case, the proposed receiver makes use of collaborative signal processing among relays to recover sources information before forwarding to the base station using a Decode-and-Forward protocol. The first receiver is based on the uncoded transmission of the tensor data reconstructed by the relays from the estimation of their factors matrix. The second one considers a tensor encoding of symbols estimated at the relays before transmission to the base station. The different proposed receivers are compared by means of computer simulations in terms of convergence and bit error rate.